Risk of medication-induced lactic acidosis and hyperlactatemia: a pharmacovigilance study of the United States Food and Drug Administration’s Adverse Event Reporting System database - Yang, Houci; Dai, Haibin; Chen, Xveying; Huang, Jiaqi; Miao, Fangzhou; Lv, Jiani; Zhang, Jiali (Frontiers in Pharmacology, 2025)
ObjectiveLactic acidosis and hyperlactatemia (LAHL) are predictors of poor clinical outcomes in critically ill patients. This research aimed to specify medications reported in association with LAHL, thus providing valuable insights into medication safety.MethodsSpontaneous reports were excavated from the United States Food and Drug Administration’s Adverse Event Reporting System (FAERS) database from Q1 2004 to Q2 2024. Adverse reaction signals of medication-induced lactic acidosis and hyperlactatemia (MILAHL) were detected by reporting odds ratio (ROR) and proportional reporting ratio (PRR).Results1,055 medications were identified as primary suspect medications of LAHL from Q1 2004 to Q2 2024, of which 180 were considered to have risk signals by ROR and 160 by PRR. Metformin (16,439 cases), linezolid (815 cases), amlodipine (646 cases), salbutamol (531 cases), and paracetamol (417 cases) were the top 5 medications with the most cases of LAHL. Among the top 50 medications with the strongest ROR and PRR signal, 16 were systemic antivirals, and 13 were antidiabetics (9 containing metformin). 23 of the top 50 medications with the strongest ROR and PRR signal did not indicate the risk of LAHL in the Summary of Product Characteristics (SmPC).ConclusionThis study listed high-risk medications by ROR and PRR analysis, especially those without an LAHL warning in SmPC, to help health professionals identify MILAHL in case of elevated lactate and enhance medication safety monitoring.